Newborn babies with tetanus in maternity children hospital Makkah: - Center experience from its application to prevent in the kingdom of Saudi Arabia - Ahojaili, Najia; zahrani, Attia Saleh Al; malki, Helal Al; Kotbi, Ibraheem; salam, Liza; Batawi, Reem (Journal of Innovations in Applied Pharmaceutical Science (JIAPS), 2018)
Neonatal tetanus (NNT), a disease preventable by immunization, is a major problem and a leading cause of neonatal mortality. To study the epidemiology, clinical appearances and outcomes of all patients diagnosed with neonatal tetanus. Moreover, to develop and supply a council to prevent NNT in the KSA. This cross-sectional study was conducted at Maternity and Children’s Hospital, Makkah, KSA; a medical centre; from 2013 to 2017. All medical data for patients with suspected diagnosis of NNT were examined to get information about sociodemographic properties. Fifty-two (52) patients were diagnosed with neonatal tetanus over 5 years in our hospital. All the cases are house delivery for unvaccinated mothers with cut the umbilical cord using unsterilized household scissors. Most of the patients presented with muscle spasms, refusal to eat and abnormal posture. All of the patients were receiving mechanical ventilation and two of them died. It is essential to begin battle to achieve complete maternal tetanus toxoid immunization at primary health centers, during antenatal care. Immunization needs to be planed so pregnant women can be informed regarding the importance of authority clinics and the risks of unhygienic house birth, and immunization should be addressed with sufficient data. Pregnant women and those of childbearing age should be the first targets for these actions.